(untitled) (The Pretoria Student Law Review, 2021)
‘Tensions [in South Africa] continue, and conflicting interests and ideologies lead to more or less unsatisfactory compromises.’ Against the backdrop of these words by Frank Welsh in his seminal work on the history of South Africa, the debate surrounding land reform will be critically examined. The African National Congress (ANC) released its ‘Land Reform Policy Discussion Document’ (hereinafter referred to as the Policy Document) in June 2012. The Policy Document outlines the ruling party’s policy on the transformation of South Africa’s land ownership, stating that: ‘[l]and reform must represent a radical and rapid break from the past without significantly disrupting agricultural production and food security.’ This article aims to take a critical look at the rhetoric and policy proposals which surround the debate on land. Furthermore, the nature and effect of the proposed redress will be examined. Through an understanding of green economics and environmentalism, the effect of economic opportunity, and a critique of the ideological defects of the proposals, this article will seek to provide a sustainable solution in contrast to the constantly unsatisfactory compromises that saturate South African public discourse around these issues.